Prevalence and Associated Factors of Thyroid Nodules Among 52,003 Chinese ‘Healthy’ Individuals in Beijing: A Retrospective Cross-Sectional Study - Xu J; Lau P; Ma Y; Zhao N; Yu X; Zhu H; Li Y (Dove Medical Press, 2024)
Jin Xu,1 Phyllis Lau,2 Yong Ma,3 Na Zhao,4 Xuezhong Yu,1 Huadong Zhu,1 Yi Li1 1Emergency Department, The State Key Laboratory for Complex, Severe and Rare Diseases, Peking Union Medical College Hospital, Chinese Academy of Medical Sciences and Peking Union Medical College, Beijing, People's Republic of China; 2Department of General Practice, The University of Melbourne, Melbourne, VIC, Australia; 3Department of Emergency Medicine, Peking University People's Hospital, Beijing, People's Republic of China; 4Department of Anesthesiology, Beijing Obstetrics and Gynecology Hospital, Capital Medical University, Beijing, People's Republic of ChinaCorrespondence: Yi Li, Emergency Department, The State Key Laboratory for Complex, Severe and Rare Diseases, Peking Union Medical College Hospital, Chinese Academy of Medical Sciences and Peking Union Medical College, Beijing, 100730, People's Republic of China, Tel + 86 10 6915 9128, Email billliyi@aliyun.comIntroduction: The prevalence of thyroid nodules has been increasing, and there are few research data on the risk factors of thyroid nodules in the Chinese population. In this study, we aimed to determine the prevalence and risk factors of thyroid nodules by retrospectively investigating the physical examination records of a cohort of "healthy" individuals in Beijing, China.Methods: This was a retrospective cross-sectional study. The database of a Medical Examination Centre (MEC) was searched. Physical examination data, blood test data, and ultrasound examination data, etc., from 2015 to 2017 were accessed. Only those that recorded a thyroid ultrasound were included. Chi-square test and t-test were used to compare clinical features of individuals' age, gender, body mass index, blood pressure, blood glucose, blood lipids, uric acid, and presence of fatty liver. Risk factors for thyroid nodules were determined using multivariate logistic regression.Results: A total of 52,003 records, which included 19,901 cases with thyroid nodules, were examined. The overall prevalence rate was 38.3% (19,901/52,003): 30.2% (6,726/22,305) and 44.4% (13,175/29,698) in men and women, respectively. Of 52,003 cases, only 35,420 cases had records of all nodule-related metabolic abnormalities and were selected for cross-sectional determination of related risk factors of thyroid nodules. In male, relationships were found between thyroid nodules and increased age (p < 0.001), impaired fasting glucose (p = 0.044), diabetes (p = 0.047), decreased HDL-C (p = 0.018) and prostatic hyperplasia (p < 0.001). And in female, relationships were found between thyroid nodules and increased age (p < 0.001) and decreased HDL-C (p < 0.001).Conclusion: Thyroid nodules are common in China. This study found that thyroid nodules are associated with several metabolic indicators or metabolic diseases, although the mechanism is unclear. Further research is needed.Keywords: thyroid nodule, prevalence, risk factor, logistic regression analysis